MPS 01-03 SERINE PROTEASE INHIBITION ATTENUATES SALT-SENSITIVE HYPERTENSION AND PODOCYTE INJURY IN A RAT MODEL OF METABOLIC SYNDROME. (September 2016) - Kakizoe, Yutaka; Mizumoto, Teruhiko; Nakagawa, Terumasa; Hayata, Manabu; Miyasato, Yoshikazu; Adachi, Masataka; Miyoshi, Taku; Kitamura, Kenichiro; Mukoyama, Masashi
Abstract : Objective: Chronic kidney disease caused by metabolic syndrome (MetS) is characterized by proteinuria, Na retention and hypertension. In the setting of proteinuria, plasminogen/plasmin filtered through damaged glomeruli could activate the epithelial Na channel (ENaC) leading to hypertension, independently of aldosterone. In this study, we evaluated effects of a synthetic serine protease (SP) inhibitor, camostat mesilate (CM) which inhibits the plasmin activity, on salt-sensitive hypertension in a rat model of MetS with high-salt (HS) diet. In addition, we studied protective effects of CM against podocyte injury in vitro. Design and Method: Five-week-old SHR and control WKY were divided into WKY, SHR, and SHR + CM (Experiment 1), and 13-week-old SHR/ND mcr-cp (model rats for MetS) were divided into normal chow (NS), HS (8.0% NaCl diet), and HS + CM (Experiment 2). After systolic BP measurement and 24 h urine collection were performed for 4 weeks, rats were sacrificed for histological examination. Urinary plasmin activities were evaluated by zymography. Cultured murine podocytes in high aldosterone and glucose media were treated with CM. Results: In Experiment 1, although SHR displayed hypertension, urinary protein excretion and plasmin activity were not substantially increased. Accordingly, CM did not prevent hypertension in SHR (SBP (mmHg): SHR 162 vs. SHR + CM 158). In Experiment 2, HS diet induced severe hypertension, marked proteinuria and plasmin activation in urine in SHR/ND mcr-cp. These changes were significantly suppressed by the treatment with CM (SBP (mmHg): HS 230 vs. HS + CM 178). CM increased urinary sodium/potassium ratio, indicating that CM inhibited the ENaC activity. Although CM mitigated apoptosis of podocytes in vivo and in vitro, CM did not inhibit the activity of Omi/HtrA2 that is a mitochondrial SP associated with apoptosis. Conclusions: In conclusion, CM could exert significant antihypertensive and renoprotective effects in a rat model of MetS, suggesting that SP inhibition could be a new therapeutic strategy against salt-sensitive hypertension in MetS.